Clinical and Immunological Profile of Anti-factor H Antibody Associated Atypical Hemolytic Uremic Syndrome: A Nationwide Database - Puraswani, Mamta; Khandelwal, Priyanka; Saini, Himanshi; Saini, Savita; Gurjar, Bahadur Singh; Sinha, Aditi; Shende, Rajashri Pramod; Maiti, Tushar Kanti; Singh, Abhishek Kumar; Kanga, Uma; Ali, Uma; Agarwal, Indira; et al. (Frontiers in Immunology, 2019)
Background: Atypical hemolytic uremic syndrome (aHUS), an important cause of acute kidney injury, is characterized by dysregulation of the alternative complement pathway. Autoantibodies to factor H (FH), a chief regulator of this pathway, account for a distinct subgroup. While high anti-FH titers predict relapse, they do not correlate well with disease activity and their functional characterization is required. Methods: Of 781 patients <18-year-old of aHUS in the nationwide database from 2007-2018, 436 (55.8%) had anti-FH antibodies. Clinical features and outcome of patients managed in the last 6-yr (n=317) were compared to before (n=119). In plasma samples of 44 patients, levels of serial circulating FH immune complexes (CIC), free FH, soluble terminal complement complex (sC5b-9), sheep red blood cell (SRBC) lysis and epitope specificity (n=8) were examined. Functional renal reserve, ambulatory hypertension, left ventricular hypertrophy (LVH) and proteinuria were evaluated in a subset. Results: Patients presented with markedly elevated anti-FH titers (10633.2±998.5 AU/ml). Management varied by center, comprising plasma exchange (PEX; 77.5%) and immunosuppression (73.9%). Patients managed in the last 6-yr showed better renal survival at mean 28.5±27.3 months (log rank P=0.022). Mean anti-FH titers stayed 700-1164 AU/ml during prolonged follow-up, correlating with CIC. Patients with relapse had lower free-FH during remission (Generalized estimating equations, P=0.001); anti-FH levels ≥1330 AU/ml and free FH ≤440 mg/l predicted relapse (hazards ratio, HR 6.3; P=0.018). Epitope specificity was similar during onset, remission and relapse. Antibody titer ≥8000 AU/ml (HR 2.23; P=0.024), time to PEX ≥14 days (HR 2.09; P=0.071) and PEX for <14 days (HR 2.60; P=0.017) predicted adverse renal outcomes. Combined PEX and immunosuppression improved long-term outcomes (HR 0.37; P=0.026); maintenance therapy reduced risk of relapses (HR 0.11; P<0.001). At 4.4±2.5 yr, median renal reserve was 15.9%; severe ambulatory, masked and pre-hypertension were found in 38%, 30% and 18%, respectively. Proteinuria and LVH occurred in 58% and 28% patients, respectively. Conclusion: Prompt recognition and therapy with PEX and immunosuppression, is associated with satisfactory outcomes. Free-FH predicts early relapses in patients with high anti-FH titers. A significant proportion of impaired functional reserve, ambulatory hypertension, proteinuria and LVH highlight the need for vigilant long-term follow-up.